Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I prove that the ideal $ (xy-1) \subset k[x,y] $ is radical? I think that it's enough to prove that the polynomial $xy-1$ is irreducible. How can we prove that?

Here $k$ is a field, I'm not sure if I have to assume that $k$ is algebraically closed, but let's assume it if it's necessary.

share|cite|improve this question
Go by contradiction write $(xy-1)=f(x,y)g(x,y)$ then write $f$ and $g$ as elements of $k[x][y]$ and look at degrees. – JSchlather Jan 18 '13 at 1:48
Your polynomial $xy - 1$ is a linear polynomial in the ring $k[y]$. – user38268 Jan 18 '13 at 1:59
Your question seems ambiguous: do you want to know why $xy-1$ is irreducible or whether irreducibility implies that the associated prime ideal is radical? Anyway the first interpretation is addressed in the comments and I have given an answer for the other interpretation. – Georges Elencwajg Jan 18 '13 at 4:38
@BenjaLim: Nitpick: the ring $k[x][y]$. (or $k(x)[y]$) – Hurkyl Jan 18 '13 at 7:04

If $A$ is a factorial ring (=UFD), then for $f\in A$ the principal ideal $I=fA $ is radical if and only if, in the decomposition $f=p_1^{a_1}\cdots p_r^{a_r}$ into non-associated irreducibles $p_i$, all multiplicities equal one: $a_i=1$.
This follows from the easy to prove general formula for the nilpotent radical: $$\sqrt I=\sqrt {p_1^{a_1}\cdots p_r^{a_r}A}=p_1\cdots p_rA$$

In particular an irreducible element $p\in A$ generates a radical ideal $pA$ and this applies to your case $p=xy-1\in A=k[x,y]$, since if $k$ is a field (algebraically closed or not), it was proved by Gauss that the polynomial ring in any number of indeterminates $k[x_1\cdots,x_n]$ is a factorial ring.

share|cite|improve this answer

For variety....

An ideal is radical if and only if its quotient ring is reduced: i.e. no nilpotents.

I claim $k[x,y] / (xy-1) \cong k[x, \frac{1}{x}]$. That is, the ring of fractions of $k[x]$ formed by inverting $x$. As this is a subring of $k(x)$, it is reduced.

Why would I claim this? Because of the calculation

$$ xy-1 \equiv 0 \pmod{xy-1} $$ $$xy \equiv 1 \pmod{xy-1} $$ $$ y \equiv \frac{1}{x} \pmod{xy-1} $$

So clearly there is a map $f : k[x,y] \to k[x,\frac{1}{x}]$ defined by $f(x)=x$ and $f(y) = \frac{1}{x}$. Because $f(xy-1) = 0$, it gives a map $k[x,y] / (xy-1)$.

The reverse direction is the map $g : k[x,\frac{1}{x}] \to k[x,y] / (xy-1)$ given by

$$g\left( \frac{a(x)}{x^n} \right) = y^n a(x)$$

First, let's check this is well-defined:

$$g\left( \frac{x^m a(x)}{x^{m+n}} \right) = y^{m+n} x^m a(x) \equiv y^n a(x) = y^n a(x) = g\left( \frac{a(x)}{x^n} \right)\pmod{xy-1} $$

It respects addition:

$$g\left( \frac{a(x)}{x^n} + \frac{b(x)}{x^n} \right) = y^n (a(x)+b(x)) = y^n a(x) + y^n b(x) = g\left( \frac{a(x)}{x^n} \right) + g \left( \frac{b(x)}{x^n} \right)$$

and multiplication:

$$g\left( \frac{a(x)}{x^m} \cdot \frac{b(x)}{x^n} \right) = y^{m+n} (a(x) b(x)) = \left( y^m a(x) \right) \left( y^n b(x) \right)= g\left( \frac{a(x)}{x^m} \right) \cdot g \left( \frac{b(x)}{x^n} \right)$$

and so $g$ is a homomorphism. Then,

$$ f\left(g\left( \frac{a(x)}{x^n} \right)\right) = f\left( y^n a(x) \right) = \frac{a(x)}{x^n} $$

and therefore $g$ is an injective homomorphism. It is surjective, since $g(x) = x$ and $g(1/x) = y$, therefore $g$ is bijective, and thus an isomorphism.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.